Parents’ Relative Socioeconomic Status and Paternal Involvement in Chinese Families: The Mediating Role of Coparenting - Liu, Chang; Wu, Xinchun; Zou, Shengqi (Frontiers in Psychology, 2016)
This study examined the mediating role of coparenting in the association between differences/similarities in paternal and maternal socioeconomic status and paternal involvement in Chinese families. The sample included 244 couples with children aged 3–7 years. Fathers and mothers reported their individual incomes, educational levels, occupations, and coparenting behavior (measured using the Coparenting Scale), and fathers completed the Father Involvement Questionnaire. Structural equation modeling was performed to examine the associations between socioeconomic status and paternal involvement. Results suggested that socioeconomic status indicator measures were outcome specific. Occupational differences/similarities were associated with paternal involvement indirectly, via fathers’ family integrity practices and reprimand behavior.　Income and educational differences/similarities did not affect paternal involvement. The results suggested that the traditional Chinese view that “men are chiefly responsible for activity in society, while women are responsible for the home” has faded.